Managing electronic resources : new and changing roles for libraries - Webster, Peter M. (Oxford : Chandos Pub., 2008)
The ongoing movement to electronic collections presents many exciting new service opportunities for libraries, as well as creating materials management, resource, and service challenges. This book looks at how online resources are causing the roles and practices of libraries to change. This book looks at new practices in managing electronic materials. It considers changes to practice which libraries, e-materials providers and software provider need to make together to meet the challenges and maximize the benefits of electronic materials. The book focuses on better integrated and more automated approaches which are becoming essential to provide more complete and seamless access to library materials.
Includes bibliographical references (p. 223-229) and index.
uaj 09/05/13
Loans
Keywords: Electronic information resources; Digital libraries; Digital libraries -- Management